2005
DOI: 10.1507/endocrj.52.537
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of Serum Free Triiodothyronine to Free Thyroxine in Graves' Hyperthyroidism and Thyrotoxicosis Caused by Painless Thyroiditis

Abstract: Abstract. The serum T 3 to T 4 ratio is a useful indicator for differentiating destruction-induced thyrotoxicosis from Graves' thyrotoxicosis. However, the usefulness of the serum free T 3 (FT 3 ) to free T 4 (FT 4 ) ratio is controversial. We therefore systematically evaluated the usefulness of this ratio, based on measurements made using two widely available commercial kits in two hospitals. Eighty-two untreated patients with thyrotoxicosis (48 patients with Graves' disease and 34 patients with painless thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 19 publications
1
35
2
2
Order By: Relevance
“…A key finding is that PM 2.5 exposure during the third trimester of gestation is inversely associated with TSH levels and the FT 4 /FT 3 ratio in cord blood, but not with thyroid hormones in maternal blood. The FT 4 /FT 3 ratio in cord blood is a useful indicator of how effectively the body is able to convert T 4 into T 3 (Yoshimura Noh et al 2005). In addition, results of the mediation analysis suggested that cord blood FT 4 is a partial mediator of the association between third-trimester pregnancy PM 2.5 exposure and birth weight, assuming the underlying causal assumptions of mediation analysis are valid.…”
Section: Discussionmentioning
confidence: 99%
“…A key finding is that PM 2.5 exposure during the third trimester of gestation is inversely associated with TSH levels and the FT 4 /FT 3 ratio in cord blood, but not with thyroid hormones in maternal blood. The FT 4 /FT 3 ratio in cord blood is a useful indicator of how effectively the body is able to convert T 4 into T 3 (Yoshimura Noh et al 2005). In addition, results of the mediation analysis suggested that cord blood FT 4 is a partial mediator of the association between third-trimester pregnancy PM 2.5 exposure and birth weight, assuming the underlying causal assumptions of mediation analysis are valid.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes it can be quite challenging, due to the possibility of painless thyroiditis and early-stage atypical GD [9]. Generally, the following methods are commonly used in the differentiation of transient thyrotoxicosis and GD: thyroid technetium 99 scan, RAIU assay, T3/T4 ratio [10], [11], serum markers such as total activity of alkaline phosphatase [12] and TRAb [4], [13], [14]. Serological assays such as FT3/FT4 ratio [10], [11] and alkaline phosphatase activity had limited values in the differential diagnosis [10], [12].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the ultrasonographic findings were considered to be enough to support a diagnosis of silent thyroiditis. Additionally, in our case, the calculated ratio of free T4 to free T3 was 2.70, which was lower than its cutoff point [15]. This may indicate the possibility of destructive thyrotoxicosis rather than Graves’ disease, for which no causal treatment was required.…”
Section: Case Reportmentioning
confidence: 64%